Innovation training in vietnam from experience of avanced countries in the world - Nguyễn Công Đức (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Entering the twenty-first century, education and training play an important role as the key factor, the driving force for the economic development. Not only in Vietnam but in most other countries in the world, all governments consider education to be the top national policy. With an advanced and developed education system that countries around the world are implementing, it is an experience for Vietnam to learn and renew a comprehensive education system. In the scope of this article, the author researches the role, characteristics and experience from the education of other countries to come up with solutions for educational development in Vietnam today.